2017
DOI: 10.1152/ajpcell.00360.2016
|View full text |Cite
|
Sign up to set email alerts
|

Biological signaling by carbon monoxide and carbon monoxide-releasing molecules

Abstract: Carbon monoxide (CO) is continuously produced in mammalian cells during the degradation of heme. It is a stable gaseous molecule that reacts selectively with transition metals in a specific redox state, and these characteristics restrict the interaction of CO with defined biological targets that transduce its signaling activity. Because of the high affinity of CO for ferrous heme, these targets can be grouped into heme-containing proteins, representing a large variety of sensors and enzymes with a series of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
145
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(153 citation statements)
references
References 137 publications
2
145
0
3
Order By: Relevance
“…Some studies have demonstrated the selective interaction of CO with structural and functional proteins, for example the interaction of CO with iron and heme‐dependent proteins (Wilkinson & Kemp, ). However, systems containing transition metals may preferentially potentiate the biological activity of the CO molecule (Motterlini & Foresti, ), as is the case of the ruthenium carbonyl compound studied. Our research group evaluated the release of the CO molecule from ct‐ [RuCl(CO)(dppb)(bipy)]PF 6 by 13 C{ 1 H} NMR (DMSO‐d 6 ) and cyclic voltammetry.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated the selective interaction of CO with structural and functional proteins, for example the interaction of CO with iron and heme‐dependent proteins (Wilkinson & Kemp, ). However, systems containing transition metals may preferentially potentiate the biological activity of the CO molecule (Motterlini & Foresti, ), as is the case of the ruthenium carbonyl compound studied. Our research group evaluated the release of the CO molecule from ct‐ [RuCl(CO)(dppb)(bipy)]PF 6 by 13 C{ 1 H} NMR (DMSO‐d 6 ) and cyclic voltammetry.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of CORM-A1, we observed the effect of different concentrations. We attribute it to the different kinetics of CO release from CORM-A1 and CORM-2 (Motterline & Foresti, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…68 In view of these findings, Hb appears to play a part in NO-dependent signalling. 164 The overall picture that emerges is that gaseous signalling plays an important role in erythrocyte function and that Hb is important in its regulation. Another signalling molecule, hydrogen sulphide, has also been demonstrated to be especially important in regulating the vasculature in response to hypoxia.…”
Section: Only For Gas Transport: Roles In Buffering and Cell Signallingmentioning
confidence: 99%